The social structure of European inequality: a multidimensional perspective - Mauritti, R; Martins, S. C.; Nunes, N.; Romão, A. L.; Costa, A. F. (Sociologia, Problemas e Práticas, 2016)
The aim of this article is to present some contributions to the understanding of social inequality in Europe today. We analyse the distributional inequalities of economic and educational resources as well as the categorical inequalities between nation states and between social classes. The source of the empirical data was the European Social Survey 2012. We were able to calculate European income deciles, build a matrix of class-country segments, and analyse the intersections of this structural matrix with the distributions of income and schooling. The results reveal high degrees of distributional inequality in Europe. They also show the structural configurations assumed in Europe by the intersection of distributive and categorical inequalities.